2021
DOI: 10.3390/ma14247849
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in Fire Protection—Application and Requirements

Abstract: Nanotechnology is used, to an increasing extent, in practically every aspect of the economy and society. One area where nanotechnology is constantly advancing is fire protection. Nanostructures are found in elements used in direct protection, such as in protective clothing, filters, and helmets. Solutions in the field of nanotechnology are also used in elements reducing the fire risk and increasing the fire safety, such as building materials and structures, paints, coatings, or fire safety equipment (e.g., fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“… Flame retardancy can be achieved through finishing treatments, wherein fabrics are treated with flame-retardant chemicals [ 11 , 12 , 13 , 14 ]. Nanoparticles with flame-retardant properties can be incorporated into coatings or applied directly to fibers to enhance their resistance to ignition [ 15 ]. Phase change materials (PCM) can be integrated into fabrics to provide additional flame resistance while maintaining wearer comfort [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Flame retardancy can be achieved through finishing treatments, wherein fabrics are treated with flame-retardant chemicals [ 11 , 12 , 13 , 14 ]. Nanoparticles with flame-retardant properties can be incorporated into coatings or applied directly to fibers to enhance their resistance to ignition [ 15 ]. Phase change materials (PCM) can be integrated into fabrics to provide additional flame resistance while maintaining wearer comfort [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles with flame-retardant properties can be incorporated into coatings or applied directly to fibers to enhance their resistance to ignition [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has become of great interest over the last decade. The global polyurea market was estimated at USD 1.22 billion in 2021 [1,2]. This interest is due to its excellent physicochemical properties, as well as development in the field of its application.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the significance of reinforcing basalt fibre in polymers to improve the mechanical and thermal properties has not been much explored [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. This is true for randomly oriented short basalt fibre polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…This is true for randomly oriented short basalt fibre polymer composites. Considering the recent literature, hybrid composites comprised of carbon/basalt/epoxy showed better fracture strain and tensile strain as compared to carbon fibre epoxy composites; however, the tensile properties were reduced [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These findings suggested that the arrangement of carbon/basalt fibre in the composite plays a crucial role in enhancing composites’ strength [ 32 ].…”
Section: Introductionmentioning
confidence: 99%